Design, synthesis and stepwise optimization of nitrile-based inhibitors of cathepsins B and L. (1st January 2021) - Cianni, Lorenzo; Rocho, Fernanda Dos Reis; Bonatto, Vinícius; Martins, Felipe Cardoso Prado; Lameira, Jerônimo; Leitão, Andrei; Montanari, Carlos A.; Shamim, Anwar
Graphical abstract: Abstract: Human cathepsin B (CatB) is an important biological target in cancer therapy. In this work, we performed a knowledge-based design approach and the synthesis of a new set of 19 peptide-like nitrile-based cathepsin inhibitors. Reported compounds were assayed against a panel of human cysteine proteases: CatB, CatL, CatK, and CatS. Three compounds (7h, 7i, and 7j ) displayed nanomolar inhibition of CatB and selectivity over CatK and CatL. The selectivity was achieved by using the combination of a para biphenyl ring at P 3, halogenated phenylalanine in P 2 and Thr-O-Bz group at P 1. Likewise, compounds 7i and 7j showed selective CatB inhibition among the panel of enzymes studied. We have also described a successful example of bioisosteric replacement of the amide bond for a sulfonamide one [7e → 6b ], where we observed an increase in affinity and selectivity for CatB while lowering the compound lipophilicity (ilogP). Our knowledge-based design approach and the respective structure–activity relationships provide insights into the specific ligand-target interactions for therapeutically relevant cathepsins.